Evaluation of a hospital-wide vancomycin-dosing nomogram in patients with continuous-flow left ventricular assist devices. Issue 6 (June 2021) - Hall, Sylvie F; Athans, Vasilios; Wanek, Matthew R; Wang, Lu; Estep, Jerry D; Williams, Brad
Introduction: Hemodynamic derangements due to heart failure are associated with alterations in pharmacokinetics. Although use of mechanical circulatory support mitigates such derangements, little evidence is available regarding pharmacokinetics in patients with LVADs. A previous pharmacokinetic analysis of vancomycin among patients with LVADs observed a reduced volume of distribution and clearance compared with estimates based on population kinetics. Methods: A total of 28 adult patients with LVADs hospitalized between January 2014 and May 2018 who received vancomycin through a pharmacist dosing consult were included. Internal medicine patients without heart failure receiving vancomycin were enrolled in a 2:1 fashion to make a control group. Exclusion criteria were unstable renal function, ESRD, acute decompensation, cardiac surgery within the preceding 5 days, or weight >110 kg. Results: No difference was observed in the proportion achieving goal trough (64% of LVAD patients vs 71% control patients, p  = 0.50). However, mean trough was significantly higher among LVAD patients (23.4 mg/L vs 17.7 mg/L, p  = 0.017). Furthermore, there was a significant difference in the distribution of trough levels ( p  = 0.025) with LVAD patients being more likely to attain levels >25 mg/L (32% vs 14%) and less likely to have troughs <10 mg/L (4% vs 14%). A numerically greater number of LVAD patients experienced nephrotoxicity but this did not reach statistical significance (32% vs 18%, p  = 0.14). Conclusion: The use of vancomycin in LVAD patients may result in higher trough levels when compared to internal medicine patients. Increased monitoring or conservative dosing may be warranted to improve safety and efficacy.